ANALISIS KEBIJAKAN PENGEMBANGAN AGROINDUSTRI MINYAK ATSIRI DI JAWA BARAT (STUDI KASUS KOMODITAS MINYAK NILAM) - Purnomo, Dwi
Abstract: Today the development of agribusiness needs a real step to stimulate investments, improving added value, and look for new local markets and abroad. An effort to stimulate high growth in agriculture sector is a compulsion. The modern agro business development system have to be developed, according to the decentralization process and responsive to global changes. One of the agriculture commodities owning a big potency is essential oil which is including into plantation agribusiness sub-sector. Essential oil is recognized also by the name of volatile oil, yielded by patchouli crop. The high value of domestic patchouli oil and in the international market do not have a significant effect to be enjoyed by farmers to increase their wealth, and the other problem is the quantity of the level storey request can not be full filled. The excelsior of world demand is not followed by the increasing of the Indonesian patchouli oil production, in fact the production of patchouli oil have been decreasing recently. The market prospect that have mentioned above is a valuable opportunity for West Java as one of the centre of patchouli oil production, because of those reasons, it is needed to have an effort development of oil industry and conducting the patchouli oil cultivation . The common objective of this research is to develop policy of essential oil agro industry, specially West Java patchouli oil commodity. Special targets of this research are: (1) Analyzing the condition of essential oil agro industry specially patchouli oil commodity in West Java, and (2) Compiling the framework formulation of policy instruments in developing essential oil agro industry which is able to improve industrial performance of patchouli oil as an excellent plantation commodity in West Java. Research population is entangled 12 people of stakeholders, and also entangled distillers and farmers which is taken in four sub-provinces in West Java Province, that is Garut, Majalengka, Kuningan, and Tasikmalaya. The Amount of samples in this research entirely counted 136 responders. Taken samples divided in two types, that is from farmers counted 120 people and 16 distillers. Data collecting of responders conducted with observation and interview. This research use three fundamental steps in formulating policy of development of agro industry patchouli oil in West Java Province, and those steps are; 1) Assessment of the existing condition of patchouli oil agro industry in this time, 2) Developed policy visioning, and 3) Formulation of policy. Pursuant to the result of visioning to patchouli oil agro industries stakeholder in West Java listed according to the level of the importance of each problem faced, and the problems are 1) The Amount of produced patchouli oil have not full filled the market demand and the supply continuity can not be guaranteed, 2) The capital weakness of producers and farmers, 3). Weakening of market system, institute and also cooperation network among industries, exporters and farmers, 5) Low quality of low patchouli oil, 4) Technology which used in patchouli oil production have different standards, its production result owning immeasurable quality, 6) Tuition for patchouli oil producer and farmer which relative still less, and 7) The government have not developed the patchouli oil agro industry clusters.Pursuant to this conducted research, we can conclude that during this time, the role of central government is insufficient, the government does not give enough attention to patchouli oil agro industry, there are no special policy to develop patchouli oil commodity which has released by government, the existing policy today, is only the policy of plantation in general and some other selected commodities. Weaken co-ordination and observation of government to other government institution officers and institutes in charge in developing the patchouli oil agro industry will make the development of patchouli oil agro industry not optimal. Policy vision of the development of patchouli oil agro industry is :\" Making patchouli oil agro industry as the pm-eminent product, namely agro industry which is able to act as motor activator of local economics growth using the development potency and big market with a good management, full fill the international standards which pay attention to the aspect of its quality, amount, and its continuity. \" Meanwhile policy missions of development of West Java patchouli oil are : 1) Pushing the make-up of quality of good human resources of government officer, and perpetrator of patchouli oil agro industry, specially to distillers and farmers through the improvement of knowledge and skilled farmer entangled government, college and agriculture research centre, 2) Settling institutes of distillers and farmers, 3) Develop patchouli oil commodity plant centers as competitive pre-eminent commodity area which is organized by farmer\'s economic organization in an agribusiness system, 4) Improving the development of patchouli oil agro industry utilized precise technology, started from conducting until handling of crops, so as the result of these processes can have an access to international market through specific environment friendly technological innovation, 5) Form efforts of agro industry patchouli oil in small scale priority in every region 6) Improving coordination of development of patchouli oil agro industry with region infrastructure, and social economic development, and 7) Improving product image of agro Indonesian patchouli oil agro industry through international market exhibitions. Here in after, this research is proposed a policy for the development of patchouli oil agro industry in West Java, Pursuant to Borda analysis method, conduded by priority sequence of patchouli oil agro industry development policy in West Java are mentioned bellow. 1) Improvement of human resource quality, 2) Settling farmer institutions, 3) Conducting patchouli crop farm extensification and intensification, 4) Development of precise utilized technology which can yield products in international standard, 4) Improvement of patchouli oil agro industry development policy coordination of with inwrought of information system and regulations, 5) Improvement of investments and capital, 6) Facilitation founding of purification factory in industrial scale in West Java, 7) Development of patchouli oil agro industry dusters, and 8) Make-Up of role of government facilitation in promoting West Java patchouli oil in the international market.